Is Glycosylated Hemoglobin A Marker of Infertility? Prospective Analytic Study (Medico Legal Update, 2020)
Infertility: Is the inability of a couple to naturally conceive, carry or deliver a healthy child after a year of unprotected intercourse (1) . Causes: Female factors :- Problems with ovulation. Blocked fallopian tubes; this can happen as the result of pelvic inflammatory disease, endometriosis, or an ectopic pregnancy. Hormonal problems such as polycystic ovarian syndrome (pcos). In ability of the fertilized egg to implant in the uterus. Cervical hostility. Premature ovarian failure. Age; A women’s fertility decline after the age of 30, both in her ability to conceive and her ability to carry pregnancy to term. Male factors: The chief factor in male infertility is sperm quality, the man may have poor motility ‹ affecting its ability to reach ovum. Alcohol, marijuana and other drug abuse can affect sperm quality. Other possible factors include erectile dysfunction and retrograde ejaculation. Female infertility account for one third of infertility cases, male infertility for another third, combined male and female infertility for another 15%, and the remainder of cases are “ un explained”.